Combating new forms of transnational criminality: The European Union against the trafficking of human beings - Magliveras, Konstantinos D. (Études helléniques / Hellenic Studies, 2006)
This article treats the highly complex problem of fighting the modern slave trade, or the trafficking of human beings. Prostitution, forced labour, illegal immigration all come under this category of transnational criminality, as people become commodities bought, sold and discarded. Along the trade routes of yesteryear, many in the Mediterranean region, human cargo crosses borders and jurisdictions. The author analyzes existing legal definitions and describes the role of various institutions, notably the European Union, which should protect the basic human rights of those who have fallen into the hands of contemporary slave traders. On this dark page of contemporary history, he does highlight the progress of political entities and legal procedures while underscoring the tremendous need for more research and cooperation among states.